The role of B2B marketing strategy, ICT B2B marketing support, and service quality in market orientation – Performance relationship: evidence from three European countries - Gregor Jagodič; Borut Milfelner (Cogent Business & Management, 2022)
The purpose of this study is to evaluate the role of marketing strategy, information communication technology (ICT) marketing support, and service quality in the market orientation-performance relationship. Even though there are many studies considering the market orientation-performance relationship they rarely take into consideration ICT marketing support and marketing strategy, especially concerning the companies operating in B2B markets. Additionally, this study compares the impacts of the constructs between two emerging economies (Slovenia and Serbia) and one developed economy (Austria) on a random sample of 636 companies. Results were obtained based on the set hypotheses using the covariance-based structural equation modeling (SEM) and invariance testing procedure to make comparisons between the three countries. Market orientation strongly influenced the successful development and implementation of marketing strategies, ICT support, and service quality. The impact of service quality on company performance was statistically insignificant and only the indirect impact of market orientation on company performance through service quality was determined. ICT marketing support and successful development and implementation of B2B marketing strategy were also positively related to company performance. This study can help managers in B2B companies in emerging and developed markets to learn how to use specific marketing resources in order to achieve higher company performance.
Keywords: 650; firm performance; service quality; market orientation; information-communication technology; marketing strategy